Screening HIV associated neurocognitive disorders using international HIV dementia scale: closing the gap through an educational intervention for healthcare workers - Namagga, Jane Kasozi; Nambozi, Grace; Rukundo, Godfrey Zari; Niyonzima, Vallence; Batwala, Vincent (Pan African Medical Journal, 2023)
Introduction: the study assessed the effect of an educational intervention on healthcare workers´ knowledge regarding the use of the International HIV Dementia Scale (IHDS) in screening HIV-associate neurocognitive disorder (HAND) at The AIDS Support Organization (TASO) centres in Uganda. Methods: we recruited healthcare workers in southwestern and central Uganda. Data were collected by a questionnaire, cleaned, and analyzed using means and standard deviations. A paired test assessed mean knowledge score differences pre-and post-intervention. We used One-Way ANOVA for mean score differences between sites and cadres. Statistical significance was taken at p ≤ 0.05 and 95% confidence interval. Prevalence of HAND for clients screened during educational intervention was computed. Results: mean age was 36.38 years (SD = 7.80) and mean years of experience 8.92 (SD = 6.52). A paired t-test showed that pre-intervention mean score (Mean= 20.38, SD 2.94) was statistically different from post-intervention mean score (Mean=22.24, SD 2.15) at t (36) = - 4.933, p > 0.001). One-way ANOVA showed counselors were statistically different from clinical officers´ pre-intervention (Mean difference 4.432 (95% CI: 0.1- 8.85, p= 0.049) and post-intervention (Mean difference 3.364 (95% CI: 0.07 - 6.65, p= 0.042) respectively. There was no difference in mean knowledge scores between sites pre-intervention (F (4, 32) = 0.827, p = 0.518) and post-intervention (F (4, 32) = 1.299, p = 0.291). Of the 500 clients screened, 72.2% were positive for HAND. Conclusion: the educational intervention improved healthcare workers´ knowledge regarding screening HAND using IHDS at TASO centers in Southwestern and Central Uganda.
Keywords: HIV-associated neurocognitive dementia; International HIV dementia scale; Knowledge; Educational intervention; Healthcare workers